Peningkatan Kreatifitas Berwirausaha Melalui Pelatihan Keterampilan Teknik Pada Siswa SMK Di Kota Payakumbuh - Sartika Anori; Yasdinul Huda; Igor Novid (Universitas PGRI Sumatera Barat, 2019)
SMK Payakumbuh graduates who work in accordance with their fields of expertise are still very few when compared with the number of graduates who have produced. Some of the causes, among others: lack of knowledge gained by students of masih, lack of supporting tools for practicum, minimal number of productive teachers, and others. In addition to the school side, this can also be influenced by external factors. Like the growth of employment that is not proportional to the number of graduates produced. This causes competition to get jobs in accordance with the field of expertise of students increasingly stringent. To help overcome this problem, the service team provides skills training and mentoring programs to enhance the creativity and innovation of students who will graduate in producing creative products based on the technical skills possessed by SMKN 2 Payakumbuh students. The methods used during the training activities are lectures, questions and answers, demonstrations, guidance. From the activities that have been carried out, students entrepreneurial creativity is better and students know the technical skills that can be developed and have a value.